Void-free ceramic-metallic composites and methods for their manufacture

By employing a vacuum-pressure-transforming furnace to minimize voids in ceramic-metallic composites, the strength and performance of these materials are significantly improved, addressing the limitations posed by voids in existing technologies.

JP7649373B2Active Publication Date: 2025-03-19FIRELINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023509527
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-14
Filing Date
2021-08-05
Publication Date
2025-03-19
Estimated Expiration
2041-08-05

AI Technical Summary

Technical Problem

Ceramic-metallic composites containing aluminum often suffer from voids formed during processing, which significantly reduce their strength and limit their utility in high-stress applications.

Method used

The use of a vacuum-pressure-transforming furnace system that applies negative pressure and positive pressure inert gas to create ceramic-metallic composites with significantly reduced voids, thereby increasing density and improving material properties.

Benefits of technology

This approach results in ceramic-metallic composites with substantially no centerline voids, leading to enhanced mechanical properties and increased performance in various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649373000001
    Figure 0007649373000001
  • Figure 0007649373000002
    Figure 0007649373000002
  • Figure 0007649373000003
    Figure 0007649373000003
Patent Text Reader

Abstract

Ceramic-metallic composites are disclosed, along with an apparatus and process for their manufacture. The invention improves the density of these composites by eliminating voids through the use of a unique furnace system that applies vacuum and positive gas pressure during certain stages of processing. In fabricating Al2O3-Al composites, each process begins with a preform containing at least 5% silicon dioxide by weight, and the final product contains aluminum oxide and aluminum, and possibly other materials.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention comprises embodiments of void-free ceramic-metallic composites and methods for their manufacture. Ceramic-metallic composites, especially those containing aluminum and aluminum compounds as constituents, have numerous applications, including brake components, including brake rotors, degassing rotors, feeder tubes, molding dies and molds, heater dip tubes, thermocouple protection tubes, ladles, stirring devices, bearings, nozzles, bushings, valve components, clutches, engine components, turbine components, electrical conductors, heat sinks, radiators, metal working dies, cutting tools, components for sporting goods (e.g., golf club heads and ice skate blades), impellers, and the like. [Background technology]

[0002] However, applicants have found that ceramic-metallic composites containing aluminum have an inherent problem of voids that arise during processing. These voids have a significant negative impact on the performance of the composite materials, particularly their strength, limiting their usefulness. Thus, an important objective of the present invention is to significantly reduce or eliminate voids, thereby increasing density and improving material properties.

[0003] As will be explained in more detail below, this objective is accomplished by creating ceramic-metallic composites in which voids have been significantly reduced (and density significantly increased) through the use of special equipment that applies negative (also called vacuum) and positive inert gas pressure to reduce or eliminate voids in the final composite.

[0004] The present embodiment is an improvement over the inventions described in U.S. Patent Nos. 5,214,011; 5,728,638; and 7,267,882. The preferred embodiment from those three prior art patents includes two main process steps:

[0005] 1. A preform shape comprising a sacrificial oxide ceramic, typically silicon dioxide (SiO2), is prepared by conventional techniques. The preform shape may consist entirely of the sacrificial oxide or may contain an inert ceramic additive, typically silicon carbide (SiC). Additionally, the preform shape may be porous or completely solid with no internal void spaces (also called pores).

[0006] 2. The preform shape is preheated in one furnace to the working temperature, which is generally between about 1000 and 1250°C, then completely immersed in a liquid aluminum (Al) bath inside a second furnace, previously brought to the same temperature range, and finally removed from the bath when processing is complete. The shape thus obtained retains its original dimensions, but during immersion the preform material is transformed into a ceramic-metallic composite. The aluminum bath may be pure or may contain traces of impurities, inert alloying elements, or 20-30% by weight of silicon (Si) to completely suppress any reaction between SiC and Al (if SiC is present in the preform). The second furnace consists of a lower section that holds the liquid aluminum and a top section that contains the heating system, which is removed when the shape is moved into and out of the bath. An inert gas, such as argon, is flowed into the furnace at atmospheric pressure to protect the liquid aluminum from excessive oxidation. During the preform immersion, the sacrificial oxide reacts with the aluminum via a displacement reaction. If silicon dioxide is used, the following reaction occurs: 4Al + 3SiO2 = 2Al2O3 + 3Si. The shape is kept in the liquid aluminum bath long enough for the displacement reaction to reach completion so that all of the sacrificial oxide is converted to aluminum oxide (Al2O3). Once the reaction is complete, the shape is removed from the liquid aluminum bath. If no silicon was initially present in the bath, the silicon produced by the reaction will be sufficiently diluted to produce an Al2O3-Al composite. If the preform contains silicon carbide, an Al2O3-Al-Si-SiC composite is produced. If the starting preform shape contained internal void space, the weight of aluminum and silicon in the final composite will depend on the size of the voids in the original preform and how much of the void space is filled with aluminum alloy during processing.

[0007] Applicants currently use this preferred embodiment to manufacture composite materials sold under the trademark TCON®. Applicants further use the term "transformation process" to describe their method of preparation, which involves a displacement reaction in a liquid metal bath.

[0008] In addition to producing unique materials with useful properties, the transformation process can produce useful shapes in net or near net shapes, which is more cost-effective than other competing processes. By using common manufacturing techniques to process the preforms into net shape shapes, the transformation process can maintain their properties, thereby eliminating or significantly reducing the various cutting or grinding steps required to utilize the final shapes. Thus, these ceramic-metallic composites produced by this prior art have various useful properties and can be molded into useful shapes in net or near net shapes for various applications. However, material defects such as voids (measured by porosity) in the final composites will limit their performance, and the larger the voids, the more adversely affected the performance will be. Applicant has discovered that following the preferred embodiments from the three prior art patents will consistently result in voids concentrated in the center region of the ceramic-metallic shapes. This is more commonly referred to as centerline porosity, and the result is as can be seen in the sample shown in cross section in Figure 1. Upon further investigation, it was also discovered that this porosity was concentrated in the free aluminum phase of the composite.

[0009] The present invention is the result of research into the root causes of voids in these ceramic-metallic composite shapes and the development of novel processing methods to eliminate these defects and thereby maximize performance. It has been discovered that centerline voids are the result of a combination of three factors: 1) dissolved hydrogen gas; 2) shrinkage as the liquid aluminum solidifies; and 3) the way heat is dissipated from the composite shape after it is removed from the aluminum bath at the end of the transformation process. As the liquid aluminum solidifies, significant shrinkage occurs while hydrogen gas is released, both of which create voids in the solid aluminum phase. The third factor is a direct result of the way the preferred embodiment from the three prior art patents is practiced, i.e., the outer surfaces of the composite shape are cooled first and the center section is cooled last, which causes shrinkage and gas voids to be concentrated in the center, resulting in centerline voids.

[0010] Hydrogen gas is highly soluble in liquid aluminum, and the main source of hydrogen is the reaction of water vapor from the air with liquid aluminum according to the following reaction: 3H2O+2Al=Al2O3+6H. This phenomenon occurs in pure aluminum as well as in alloys of aluminum with other components. As the temperature of aluminum increases, the solubility of hydrogen also increases: for example, the solubility of hydrogen in liquid pure aluminum is 0.65 mL of hydrogen per 100 g of aluminum at 660 °C, compared to 3 mL / 100 g at 900 °C. Furthermore, the solubility of hydrogen in pure aluminum decreases significantly as the metal solidifies: at 660 °C, the solubility in liquid aluminum is 0.65 mL / 100 g, but when the aluminum solidifies, it is only 0.034 mL / 100 g. Thus, as the liquid aluminum cools, hydrogen gas is driven off and voids form as the metal solidifies. The effect of voids resulting from dissolved hydrogen on the mechanical properties of aluminum is significant. As an example, a 356 aluminum alloy with nearly zero dissolved hydrogen would have a tensile strength of 41,000 psi, whereas the same alloy cast with 0.27 mL / 100 g of dissolved hydrogen would have a strength of 35,000 psi, a 15% decrease.

[0011] Problems associated with the dissolution of hydrogen into liquid aluminum and the subsequent generation of voids in the solid aluminum, as well as techniques to reduce or eliminate the voids, have been widely reported in the prior art. In the field of metal casting of aluminum and aluminum alloys, there are several techniques that are widely used in the industry. Gas purging is the most widely used technique, where an inert gas (e.g., argon) or an inert-inert gas mixture (e.g., argon + chlorine) is bubbled through the liquid aluminum to drive the dissolved hydrogen out of the liquid. Applying a vacuum to liquid aluminum is also a known practice, but is not commonly used by metal casting manufacturers.

[0012] The second source of porosity in ceramic-metallic composites is due to shrinkage upon solidification; the effect of this type of porosity is much more significant than that caused by dissolved hydrogen. As liquid aluminum and aluminum alloys cool and solidify, there is a significant increase in the density of the material; in other words, as the liquid solidifies, there is a significant decrease in volume (also called shrinkage). If this shrinkage is not compensated for upon solidification, the solid metal will contain porosity. Most of the volumetric shrinkage occurs at the melting point: the melting point of pure aluminum is 660°C, and when liquid aluminum solidifies at that temperature, its density is 2.368 g / cm. 3 from 2.548 g / cm 3 to 5%, resulting in a volumetric shrinkage of 7.1%. Aluminum alloys also experience volumetric shrinkage upon solidification, which can range from 3.5 to 8.5%, depending on the alloying elements. Again, unless the volumetric shrinkage is backfilled with additional aluminum, the voids will be similar in size. The voids are severe enough to negatively affect the mechanical properties of the solid metal. As an example, as the voids in 319 aluminum casting alloy increase from about 0 to 5 volume percent, the tensile strength decreases by more than 50% (from 225,000 psi to less than 100,000 psi) and the metal becomes more brittle.

[0013] The phenomenon of shrinkage porosity in aluminum and aluminum alloy castings has also been widely reported in the prior art. The main technique used to reduce or eliminate porosity in aluminum castings is the use of feeders. Metal castings are produced by injecting liquid metal into a mold, and the feeder is a container of liquid designed to solidify last after the casting has completely solidified in the mold, and as the liquid metal in the mold cavity solidifies and shrinks, liquid is drawn from the feeder to compensate for the shrinkage. A further technique uses mold materials and designs that affect the solidification process of the liquid metal inside the mold in order to eliminate porosity resulting from solidification shrinkage. However, these techniques are not practical in the case of ceramic-metallic composites produced according to the preferred embodiments of the prior art patents, because the process does not use any type of mold when the displacement reaction is carried out.

[0014] Finally, the location of the shrinkage voids is a direct result of following the preferred embodiments from those three prior art patents. As discussed above, the preform shape containing the sacrificial oxide ceramic is fully immersed in a liquid aluminum bath held at about 1000-1250°C, and once the displacement reaction is complete, the shape is removed from the bath. Initially, the final ceramic-metallic composite shape emerges from the bath at a homogenous temperature equal to the temperature of the liquid aluminum bath, but its outer surface immediately begins to cool. Because the shape is self-supporting, residual heat will continually dissipate from its outer surface, creating a temperature gradient whereby the areas closest to the outer surface are cooler than the areas in the center of the shape. As the temperature drops to the solidification temperature of aluminum (e.g., 660°C for pure aluminum and 577°C for aluminum-silicon alloys), the aluminum in the areas closest to the outer surface will solidify first, and the resulting shrinkage will be backfilled by the liquid aluminum in the center of the shape. Cooling proceeds and continues until all of the aluminum in the composite shape is completely solidified. However, a centerline void is formed because it is the last area for the aluminum to solidify and it is not possible to backfill the void with additional aluminum. As an example, FIG. 1 shows a centerline void that was formed in a test bar machined according to preferred embodiments from three prior art patents.

[0015] The applicant of the present application has known the following prior art.

[0016] Formation of Lanxide TMCeramic Composite Materials (Newkirk et al.) (Journal of Materials Research, Vol. 1, Issue 1, February 1986, pages 81-89) describes the Lanxide DIMOX (intended for metal oxidation) process for preparing ceramic-metal composites. This fabrication technique utilizes a vapor phase transport process and involves the oxidation of bulk liquid metal with a gas to produce ceramic-metal composites, such as aluminum oxide (Al2O3)-aluminum (Al) ceramic-metallic composites.

[0017] US Pat. No. 4,713,360 (Newkirk) further discloses a preferred embodiment of the Lanxide DIMOX (directed for metal oxidation) process.

[0018] U.S. Patent No. 2,702,750 (George) discloses a method for making aluminum oxide (Al2O3)-aluminum (Al) ceramic-metallic composites produced by a displacement reaction in a liquid metallic Al bath at preferred temperatures of 700-900°C. The present invention differs from the teachings of George in that the process of the present invention is carried out at significantly higher temperatures (typically 1000-1200°C) than George's. However, composites produced according to the preferred embodiment of this patent will also suffer from centerline voids due to shrinkage of the aluminum upon solidification.

[0019] U.S. Patent No. 5,214,011 (Breslin) discloses a method for making aluminum oxide (Al2O3)-aluminum (Al) ceramic-metallic composites by a displacement reaction in a liquid metal bath at a suitable temperature at least 300°C above the melting point of aluminum (Al) (660°C). The process disclosed in that patent is carried out at temperatures of 960°C or higher.

[0020] US Pat. No. 5,728,638 (Strange) discloses an improvement over the invention disclosed in Breslin's '011 patent by incorporating an inert metal additive that provides improved performance.

[0021] US Patent No. 7,267,882 (Breslin) discloses an improvement over the invention disclosed in Breslin's '011 patent by incorporating an inert ceramic additive, such as silicon carbide, which provides improved performance.

[0022] Breslin '011, Strange '638, and Breslin '882 all discuss a method of making ceramic-metallic composites using shapes containing sacrificial oxides (commonly referred to as a "transformation process"). Although Breslin '011 and Strange '638 focus on Al2O3-Al composites, and Breslin '882 focuses on Al2O3-Al-SiC composites, they all fail to recognize that the free aluminum or aluminum alloy in their composites has a high tendency to form voids as the composites are processed, and that this void is a significant limiting factor in whether the composites can be used in high stress applications. Moreover, following the implementation of those prior art patents, the ceramic-metallic composites so obtained will have centerline voids, as previously discussed, which will negatively affect the material properties.

[0023] Co-continuous Al / Al2O3 composite produced by liquid displacement reaction: Relationship between microstructure and mechanical behavior (GM LaVecchia, C. Badini, D. Puppo, F. D'Errico, 2003). These researchers conducted experiments on ceramic-metallic composites made according to the preferred embodiment of the Breslin '011 patent, specifically the transformation of a silicon dioxide preform (in the form of molten quartz glass) in a bath of liquid metal consisting of either pure aluminum or an alloy of aluminum plus 10% silicon. In all samples made, the researchers found up to 1.7% by volume of residual voids in the final composite. Moreover, the researchers documented how the voids negatively affected the mechanical properties of the composites, such as reducing tensile strength, and also caused variability in the test results. This reference documents the problems the assignee of the present application experienced in the practice of the preferred embodiment of the Breslin patent.

[0024] Structure-Property Relationship of Binder Jetted Fused Silica Preforms to Manufacture Ceramic-Metallic Interpenetrating Phase Composites (Kyle Myers, 2016). The researchers conducted experiments on ceramic-metallic composites made according to the preferred embodiment of Breslin's '011 patent, specifically by fabricating silicon dioxide preforms by additive manufacturing (also known as 3D printing) followed by transformation in a liquid metal bath of pure aluminum. Voids were found in all of the composite samples made by the researchers, and the researchers documented how the voids negatively affected physical properties such as strength and stiffness. Attempts were made to use hot isostatic pressing (HIP) as a post-processing technique, but this was not able to remove all of the voids in the composite samples. The researchers also tried using vacuum and inert gas pressure (3.45 MPa) during the transformation process, but the samples still contained voids. This reference documents the problems the assignee experienced in practicing preferred embodiments of the Breslin patent, and further supports that the use of vacuum and pressure to create void-free ceramic-metallic composites is a patentable invention.

[0025] Co-Continuous Composite Materials for Friction and Braking Applications (GS Daehn and MC Breslin, 2006). These researchers conducted experiments with ceramic-metallic composites made according to the preferred embodiments of Breslin '011 and Breslin '882 patents, specifically by making a preform containing silicon dioxide plus silicon carbide, followed by transformation in a bath of liquid metal consisting of aluminum plus 25% silicon. Small samples were tested in a benchtop friction pair apparatus, and the results showed that these ceramic-metallic composites are promising lightweight materials that could be useful as rotors for automotive brakes. However, it has been the assignee's experience that when full-size automotive brake rotors are made in accordance with the preferred embodiments of the Breslin '011 and Breslin '882 patents and samples of the rotors are tested in a dynamometer simulating automotive braking conditions, the automotive brake rotors fail the tests because the physical properties of the rotors are significantly reduced due to the voids.

[0026] All of the following prior art discloses sufficient data to support Applicant's claims regarding the improvements of the present invention.

[0027] ASM Specialty Handbook:Aluminum and Aluminum Alloys(Edited by JRDavis,1993);Metals Handbook Ninth Edition,Volume 15:Casting(Edited by DMStefanescu,1988);Metals Handbook Desk Edition(Edited by HEBoyer and TLGall,1985);Microstructure Development During Metalcasting (JE Gruzleski, 2000); and Using Partial Pressure in Vacuum Furnaces (DH Herring, published by Industrial Heating magazine, November 2005).

[0028] These books and articles describe the properties of aluminum and aluminum alloys, including the shrinkage of liquid aluminum as it solidifies, the solubility of hydrogen in liquid aluminum, and how gases create voids as aluminum solidifies and how voids negatively affect the properties of aluminum and aluminum alloys, as well as conventional techniques for heat treating and vacuum processing. Summary of the Invention [Means for solving the problem]

[0029] The present invention comprises embodiments of void-free ceramic-metallic composites and methods for their manufacture. Ceramic-metallic composites containing aluminum or aluminum alloys are materials that have a variety of useful properties. However, when prior art processes are followed, these composites become void-containing, which significantly reduces their properties and usefulness. The present invention includes the following objects, aspects, and features:

[0030] (1) To address this issue, the present invention contemplates the use of a unique furnace system to carry out the displacement reaction for producing these ceramic-metallic composites, specifically aluminum oxide (Al2O3)-aluminum (Al) composites or aluminum oxide (Al2O3)-aluminum (Al)-silicon carbide (SiC) composites produced by displacement reaction in a liquid metal bath. In some embodiments of the present invention, a unique transformation furnace system is used that integrates a preheating system with a liquid metal bath held at a temperature of at least 900°C and above, all contained within a chamber that can be fully evacuated and even pressurized with an inert gas. This unique furnace system can be called a Vacuum-Pressure-Transformation furnace, or VPT furnace for short.

[0031] (2) these novel methods are not obvious from existing technology reflected in the prior art discussed above, particularly the Breslin and Strange patents, and are currently used by applicants to make ceramic-metallic composites sold under the trademark TCON®.

[0032] (3) The displacement reaction between the metal and the sacrificial oxide results in a composite material with co-continuous ceramic-metal phases, which have unique properties. The applicant's preferred method uses a preform shape containing silicon dioxide (SiO2) and performs the displacement reaction by completely immersing the preform in a bath of liquid aluminum; this method for performing the displacement reaction is known as the "transformation" process. To avoid reactant starvation, it is best to have the bath contain more than the minimum amount of liquid metal required. Furthermore, the preform shape is kept in the bath until all the sacrificial oxide has reacted.

[0033] (4) In one variation of this process, the following reaction is used to produce an aluminum oxide ceramic-aluminum metal (Al2O3-Al) based composite: (4+x)Al+3SiO2=2Al2O3+xAl+3[Si] Al Note that silicon (Si) by-product dissolves in the liquid aluminum (Al); most of it flows into the Al bath and some remains in the final composite. This results in a material with a composition by weight of 74% Al2O3, 26% Al, and traces of Si reaction by-product.

[0034] (5) In another variation of this transformation process, silicon carbide (SiC) particulate matter can be added to these Al2O3-Al based composites to affect the final performance, for example to improve the thermal shock resistance of the material. Under the appropriate processing conditions, the SiC additive is inert and does not participate in the substitution reaction. More specifically, to prevent SiC from reacting with Al, the liquid aluminum bath contains excess Si to suppress the reaction 4Al+3SiC=Al4C3+3Si. The reaction can then be expressed as: (4+x)Al+3SiO2+y[Si] Al +zSiC=2Al2O3+xAl+(3+y)[Si] Al +zSiC

[0035] (6) The resulting material maintains the basic Al2O3-Al structure, which is bound together by the SiC additive. Whether the composite contains silicon carbide or not, the transformation process is typically carried out at temperatures above 900°C to form alpha-aluminum oxide (α-Al2O3) from the substitution reaction. Furthermore, the resulting shapes retain the original dimensions of the preform shape, but during immersion, the preform material is transformed to become a ceramic-metallic composite. Finally, all of these types of ceramic-metallic composites are commercially manufactured by the present assignee, Fireline, Inc., and sold under the trademark TCON®.

[0036] (7) As previously mentioned, preferred embodiments from Breslin '011, Strange '638, and Breslin '882 use a preheat furnace and another transformation furnace containing liquid aluminum. The preform shape is preheated in the first furnace to the working temperature, typically between about 1000-1250°C, then fully immersed in a liquid aluminum (Al) bath inside the second furnace, which has been preheated to the same temperature range, and finally removed from the bath when processing is complete. The second furnace consists of a lower section that holds the liquid aluminum and a top section that contains the heating system, which is removed when the shape is moved into and out of the bath. An inert blanket gas, such as argon, is flowed into the furnace at atmospheric pressure to protect the liquid aluminum from excessive oxidation. Although the liquid aluminum bath can be degassed using conventional methods described in the prior art, thereby minimizing hydrogen gas voids, centerline voids will form due to the way the composite shapes are cooled after being extracted from the liquid metal bath. The Vacuum-Pressure-Transformation Furnace is a unique furnace system that addresses both issues, resulting in a ceramic-metallic composite that is substantially void-free and has optimal properties.

[0037] (8) Figures 2 and 4 show composite material processed through this vacuum-pressure-transformation furnace that exhibits no centerline porosity, whereas Figures 1 and 3 show samples processed according to the prior art and that exhibit centerline porosity.

[0038] (9) As previously mentioned, preferred embodiments from Breslin '011, Strange '638, and Breslin '882 use a system of two separate furnaces, the first of which is used to preheat the preform shapes to a working temperature, typically between about 1000-1250°C, while the second furnace consists of a lower section which holds the liquid aluminum at the same temperature range and a top section which contains the heating system; the top section is removed when shapes are moved into and out of the bath. An inert jacket gas, such as argon, at atmospheric pressure is flowed into the furnace to protect the liquid aluminum from excessive oxidation.

[0039] (10) The VPT furnace system is an improvement over those prior art furnace systems for several reasons: the shape preheat and transformation steps are performed in one furnace system instead of two separate furnaces; the use of vacuum pressure to remove air and moisture is much more effective than the use of an inert jacketing gas, thereby significantly increasing the cleanliness of the liquid metal bath; the use of positive inert gas pressure eliminates the formation of centerline voids in the final composite shape.

[0040] (11) Moreover, a further surprising benefit of the vacuum-pressure-transformation furnace has been discovered: the transformation reaction rates achieved are significantly higher than in the prior art. Breslin '011, Strange '638, and Breslin '882 all disclose that reaction rates of 1-3 mm / hr are achieved according to the preferred embodiments of those patents. In the present invention, surprisingly, rates of 8.5 mm / hr or more are achieved with the same preform composition, which is an improvement of nearly three times. As a result, the use of the vacuum-pressure-transformation furnace has a significant advantage as a manufacturing process, since the processing speed of the shaped object can be increased by three times over the prior art.

[0041] (12) Although prior art patents disclose how negative and positive pressure can be used in processing ceramic-metallic composites, the prior art patents do so in a different context than disclosed by the present application. For example, the Breslin '011 patent contains the following disclosure beginning at column 8, line 52: "Another advantage of the present invention is that the reaction can be carried out in an oxygen-free environment, e.g., under an argon blanket or Ar / H mixture, or under full or partial vacuum. Thus, the present invention avoids undesirable oxidation side reactions that can occur in the Lanxide DIMOX process and other prior art processes."

[0042] The disclosure made in Breslin's '011 patent is purely to contrast the uniqueness of its invention with other prior art in which a significant amount of an oxidizing atmosphere is required.

[0043] (13) Additionally, Breslin's '882 patent discloses the following, beginning at column 4, line 17: "The process has been successfully completed at pressures between 5 psi and about 5 micrometers Hg (absolute) above atmospheric pressure. The process has also been successfully completed in an inert atmosphere. It is believed that the process may also be successfully completed at higher pressures, and as discussed below, the process and reaction does not rely on forcing liquid metal into pores in the preform, since the preform is preferably immersed in the liquid metal and there is no atmosphere surrounding the reaction other than the liquid metal."; Furthermore, beginning at column 5, line 59, there is the following: "Traditional composite preparation techniques generally require continuous porosity through the preform to allow the metal to flow into the preform and maximize contact with the ceramic matrix, so large porosity is desired and therefore there must be restrictive pressure free flow paths or pockets that the liquid metal cannot penetrate. These processes often use positive or negative pressure to force the metal into or through the pores. Unlike traditional composite formation, the aluminum in the present invention does not need to pass through pores in the ceramic to contact the reactants, and porosity in the preform is undesirable in the present invention because the composite formation is reaction driven and not pore filling driven."

[0044] (14) These disclosures by Breslin '882 are made to contrast the uniqueness of its invention with other prior art where the presence of pores in the preform is a prerequisite, in addition to the use of negative and / or positive pressure to force liquid metal into the pores of the preform to create a ceramic-metallic composite. Applicants agree with Breslin '011, Strange '638, and Breslin '882 in that their preferred embodiments, unlike the prior art, do not require vacuum or pressure to effect the displacement reaction; the transformation process proceeds satisfactorily in both solid and porous preform shapes without the need for vacuum or pressure. However, those prior art patents fail to recognize that the formation of voids in the final ceramic-metallic composite is part of their preferred embodiments. This application provides a unique solution to that problem.

[0045] (15) A number of potential industrial applications for these improved ceramic-metallic composites are outlined in the prior art patents disclosed and discussed above. A focus of current product and market development for assignee Fireline, Inc. is automotive brake rotors, and the composites of the present invention provide significant performance improvements in that application.

[0046] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, it is a primary object of the present invention to provide void-free ceramic-metallic composites and methods for making them.

[0047] It is a further object of the present invention to provide such a composite material, recognizing that the presence of voids in the material reduces the strength of the composite material.

[0048] A further object of the present invention is to address improvements to ceramic-metallic composites, unique to those incorporating aluminum oxide and aluminum, produced by a displacement reaction in a liquid metal bath by using a unique furnace called a Vacuum-Pressure-Transformation Furnace.

[0049] It is a still further object of this invention not only to provide such composite materials, but also to disclose and claim methods for their manufacture.

[0050] These and other objects, aspects and features of the present invention will become better understood from the following detailed description taken in conjunction with the accompanying drawings. [Brief description of the drawings]

[0051] [Figure 1] 1 is an optical photograph at 5x magnification of a cross-sectioned prior art test bar showing centerline voids. [Diagram 2] 1 is an optical photograph at 5x magnification of a test bar made in accordance with the teachings of the present invention, cross-sectioned, showing no centerline voids. [Diagram 3] 1 is an optical photograph at 5x magnification of a broken prior art test bar showing centerline voids. [Figure 4] 1 is an optical photograph at 5x magnification of a broken test bar made in accordance with the teachings of the present invention that shows no centerline voids. [Diagram 5] FIG. 2 is a cross-sectional view of a vacuum-pressure-transformation furnace with a shape actuator, the shape being in a preheat position. [Figure 6] FIG. 2 is a cross-sectional view of a vacuum-pressure-transformation furnace with actuator, where the shape is immersed in liquid metal. [Figure 7] FIG. 2 is a cross-sectional view of a vacuum-pressure-transformation furnace without an actuator, with the shape in a preheated position above the solid metal. [Figure 8] FIG. 2 is a cross-sectional view of a vacuum-pressure-transformation furnace without an actuator, where the shape is immersed in liquid metal. [Figure 9] FIG. 1 is a cross-sectional view of a vacuum-pressure-transformation furnace without an actuator, with the shape going through a repressurization treatment cycle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] Vacuum-pressure-transform furnaces are designed to carry out the transformation process and are operated under two main pressure conditions, either negative (i.e., vacuum) or positive pressure, although either mode may be used during a complete furnace cycle. At the beginning and even end of each furnace cycle, the furnace chamber is allowed to reach ambient atmospheric pressure when it is opened to load and unload shapes. An example of a vacuum-pressure-transform furnace is shown in FIG. 5, with the subcomponents numbered individually: The chamber system 10 is capable of withstanding negative and positive inert gas pressures (both during high temperature operation); a chamber lid 11 or door; allowing the crucible, metal charge, fixtures, and preforms or composite shapes to be inserted and removed from the chamber; a heating system 13, integrated with the chamber, capable of heating the metal to a liquid state and even to temperatures of at least 900° C. and above, plus being capable of preheating the preform shape prior to immersion in the liquid metal bath; crucible 15; containing metal 17 for the transformation process; Vacuum pump system 19; Inert gas supply and pressurization system 21; Fixture 23; used to hold preform / composite shape 25 during processing.

[0053] Finally, an optional actuator mechanism 27 is used to completely immerse the preform shape into the liquid metal bath and then extract the ceramic-metallic composite shape from the liquid metal bath.

[0054] Although the exact configuration of the VPT furnace can be varied, it is the combination of their properties that results in the successful fabrication of void-free ceramic-metallic composites.

[0055] The vacuum-pressure-transformation furnace is designed to achieve specified levels of vacuum pressure (as low as possible) and positive inert gas pressure (as high as possible), but the exact values ​​used during processing will depend on a variety of factors, as discussed below.

[0056] A perfect vacuum is defined as a space completely free of matter, whereas industrial applications use partial vacuums, where some matter still remains. Furthermore, it is more meaningful to define the quality of a vacuum by how close it is to a perfect vacuum, measured in partial pressures (below atmospheric pressure) in units such as torr. With standard atmospheric pressure being 760 torr, vacuum qualities are typically classified as follows: rough vacuum (760 torr - 25 torr), medium vacuum (25 torr - 0.001 torr), high vacuum (1×10 -3 ~1×10 -9 torr), and ultra-high vacuum (1×10 -9 ~1×10 -12The vacuum is applied at a pressure of 1000 psi (2000 psi torr) during the initial part of the vacuum-pressure-transform furnace cycle. There are three benefits to applying a vacuum during the initial part of the cycle. The first is the removal of moisture from the chamber, which significantly reduces the amount of hydrogen dissolved in the liquid aluminum. The second is the removal of oxygen from the chamber, which from the air and moisture causes an oxide layer to form on the upper surface of the liquid aluminum bath. This oxide layer, also known in the art as dross, forms a tough skin on the upper surface of the melt that will thicken with increasing temperature and exposure to oxygen. Any attempt to immerse a preform shape in the liquid bath will destroy the oxide layer, with pieces sticking to the outside of the shape or penetrating into the shape, either of which can cause quality problems in the final product. The use of a vacuum reduces this oxide layer to a minimum thickness. A third benefit is the evacuation of oxygen and moisture from the surface of the preform shape as well as from pores within the material, thereby eliminating another possible source of hydrogen gas or oxide defects. Thus, optimizing the use of vacuum at the start of the vacuum-pressure-transformation furnace cycle virtually eliminates the formation of hydrogen gas voids and dross defects in the final ceramic-metallic composite, although these results are typically achieved at medium (25-0.001 torr) or high (1×10 -3 ~1×10 -9 This is achieved by using a vacuum of, say, 1×10 torr. The three benefits outlined above can be achieved by applying a vacuum in the VPT furnace while the system is cold, but as temperatures rise to above 900°C there is a risk of exceeding the boiling point of the material in the VPT furnace. For example, the boiling point of liquid aluminum at 760 torr is 2327°C, but as the vacuum pressure is reduced to 0.1 torr the boiling point drops to 1123°C. In this example, a vacuum of, say, 1×10 -4It is advisable to use a high vacuum, such as 500 torr, but as the temperature increases and exceeds 900°C, reduce to a medium vacuum, such as 5 torr, and use a VPT furnace cycle. Therefore, during the VPT furnace cycle, careful consideration must be given to the boiling point of the materials contained within the VPT chamber and the vacuum level achieved.

[0057] Finally, a benefit of applying positive inert gas pressure during and after the shape is removed from the liquid metal bath in the VPT furnace is to eliminate centerline voids as the shape cools. When a composite shape is removed from a liquid metal bath, its outer surface cools first, and perhaps faster than its interior regions. Thus, the liquid metal located inside the composite shape, near the outer surface, begins to solidify first. Centerline voids form because the central region of the composite shape solidifies last, and it is not possible to backfill the voids with additional metal. By applying positive inert gas pressure and controlling the cooling rate, the liquid metal inside the composite shape is forced toward the central region while solidifying more uniformly, thereby eliminating the possibility of centerline voids. The present application has found that this benefit can be achieved with positive pressures as low as 0.3 MPa (50 psi) to as high as 6.9 MPa (1000 psi) or more.

[0058] The vacuum-pressure-transformation furnace can be configured to operate in two modes of operation, as shown in Figures 5-9.

[0059] In the first mode, shown in Figures 5 and 6, the transformation of the preform shape is effected by using actuator 27. Using this mode, the entire process is carried out in one furnace cycle, resulting in a ceramic-metallic composite without centerline voids.

[0060] The second mode, shown in Figures 7, 8, and 9, must be carried out in two furnace cycles. The first cycle of transformation of the preform shape 25 is carried out without an actuator, as seen in Figures 7 and 8. This is followed by a second cycle using a remelting-repressurizing process on the same composite shape 25, as seen in Figure 9; the crucible 15 and metal bath 17 are removed and the composite shape 25 is placed back into the furnace chamber.

[0061] Either mode will result in composite shapes that do not contain centerline voids. The first vacuum-pressure-transformation furnace configuration mode, in which the entire process is carried out in one furnace cycle, appears to be the most convenient, but integrating actuators into the system is also a design and operational challenge since it must withstand both vacuum and high positive pressure under high temperature conditions. Therefore, operating the VPT furnace in the second configuration mode, which uses a two furnace cycle, is an alternative.

[0062] In the second construction mode, a first furnace cycle is used to transform the preform material into a ceramic-metallic composite without the use of actuators. The composite shape remains in the liquid metal bath at the end of the transformation cycle and is then removed from the liquid at ambient pressure conditions. Although the furnace cycle uses vacuum pressure to remove the dissolved hydrogen gas, centerline voids are created due to the contraction of the liquid aluminum upon solidification and because the central region of the shape is cooled last. Therefore, in the absence of actuators in the VPT furnace, a second furnace cycle to perform the remelting-repressurization process is essential to eliminate centerline voids in the final composite shape.

[0063] During the second furnace cycle, the ceramic-metallic composite shape is heated to a temperature just above the melting point of the metal component, and the furnace cycle is started at negative pressure to remove oxygen and moisture from the chamber, then switched to positive inert gas pressure to complete the cycle. The shape is heated to a high temperature and for a long time sufficient to melt the metal components in the composite. By applying positive inert gas pressure and controlling the cooling rate, the liquid metal inside the composite shape is forced toward the center region while solidifying more uniformly, thereby eliminating the possibility of centerline voids forming again. After the remelt-repressurization process, the ceramic-metallic composite will have improved properties.

[0064] The prior art definition of the term "heat treatment," as defined in the Metals Handbook Desk Edition, is "the heating and cooling of a solid metal or alloy to obtain a desired condition or property." Additionally, the prior art process of "hot isostatic pressing" of solid aluminum alloys, as defined in Metals Handbook Ninth Edition, Volume 15:Casting, is carried out at high inert gas pressures, but at temperatures below where incipient melting occurs. In both cases, these prior art processes require that the metal shape remain solid and be processed below its melting point. In contrast, the present invention's use of the remelt-repress process is unique in that the process is specifically used to eliminate porosity in a ceramic-metallic composite by heating the material to a point where the metal components in the composite shape melt, and by applying negative and positive pressures.

[0065] The minimum processing temperature used in the remelt-repressurization furnace cycle will depend on the metal composition of the ceramic-metallic composite and, more specifically, the melting point of the metal or metal alloy. For example, pure aluminum melts at 660°C, when aluminum is alloyed with magnesium, its initial melting point is 450°C, and when aluminum is alloyed with silicon, its initial melting point is 577°C. Therefore, careful consideration must be given to the composition of the metal alloy in the ceramic-metallic composite and the associated liquidus temperature.

[0066] No benefit is found from using a vacuum-pressure-transformation furnace when using a conventional transformation furnace from the prior art. The elimination of porosity in a ceramic-metallic composite by using a VPT furnace has a very significant effect on the final material properties. For example, a test bar similar to that shown in FIG. 1 had a three-point bend strength of 275 MPa or 39,900 psi (per ASTM C1161 procedure) and 1.5 volume percent porosity (measured by Archimedes' principle) (per ASTM C20 procedure), whereas a test bar similar to that shown in FIG. 2 had a three-point bend strength of 423 MPa or 61,400 psi and no measurable porosity. Eliminating centerline porosity using this unique furnace system maximizes the strength of the composite due to the increased density.

[0067] The two embodiments of the present invention described below provide significant variation in the final density of ceramic-metallic composites over prior art embodiments, resulting in unique composites with reduced amounts of voids and therefore improved performance over that obtained from prior art embodiments.

[0068] In one preferred embodiment, the vacuum-pressure-transformation furnace incorporates an actuator for manipulating the preform shape during controlled immersion in the liquid metal bath and removal of the part from the bath upon completion of the transformation reaction. The configuration of the actuator will vary depending on a combination of factors including the desired complexity and cost, but in any case its function will be to restrain the shape during immersion in and removal from the liquid metal bath. When this actuator is used, the VPT furnace cycle essentially consists of seven stages.

[0069] Stage 1: The preform shape is mounted in a fixture, a crucible containing an aluminum charge is prepared, and all is loaded into a VPT furnace under ambient atmospheric pressure, and then the chamber is sealed.

[0070] Stage 2: While the preform is held above the crucible by the actuator, the chamber is evacuated and the heating system preheats the preform to a temperature higher than 900 °C and melts the aluminum. Initially, a high vacuum (1 × 10 -3 ~1×10 -9 It is best to use a vacuum of 0.001 torr, but once the metal has melted and the temperature has reached 900°C, the vacuum quality must be reduced to a medium vacuum (25 torr - 0.001 torr), the final value depending on the final holding temperature and the boiling points of the components in the melt.

[0071] Stage 3: With the chamber under vacuum and both the preform shape and the aluminum bath above 900° C., the preform is completely immersed in the liquid aluminum bath by an actuator.

[0072] Stage 4: As soon as the shaped object is completely immersed in the liquid aluminum bath, apply positive inert gas pressure and keep the temperature and pressure constant until the displacement reaction is complete. It is recommended to use argon or helium gas in the pressure range of 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or more.

[0073] Stage 5: With the chamber still under positive pressure, the actuator pulls the shape completely out of the liquid aluminum bath.

[0074] Stage 6: The shape is allowed to cool while the chamber remains under positive pressure.

[0075] Stage 7: Once the shape temperature has dropped below the solidification temperature of aluminum, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, and the ceramic-metallic composite shape is removed. This temperature is 660°C for pure aluminum and lower for aluminum alloys depending on the alloying elements. The final composite has no centerline voids and improved properties.

[0076] In a second preferred embodiment, the vacuum-pressure-transform furnace does not include an actuator to handle the movement of the preform shape into and out of the liquid metal bath. Because of this, the shape cannot be pressurized after it is removed from the bath and must go through a second VPT furnace cycle. In this embodiment, the first VPT furnace cycle is essentially made up of six stages.

[0077] Stage 1: A charge of solid aluminum is loaded into a crucible, a preform shape is attached to a fixture and then placed on top of the solid aluminum, and the entire assembly is loaded into a VPT furnace at ambient atmospheric pressure and the chamber is then sealed.

[0078] Stage 2: The chamber is evacuated and the heating system heats the preform shape and aluminum to a temperature above 900°C. Initially, a high vacuum (1×10 -3 ~1×10 -9 It is best to use a vacuum of 0.001 torr, but once the metal has melted and the temperature has reached 900°C, the vacuum quality must be reduced to a medium vacuum (25 torr - 0.001 torr), the final value depending on the final holding temperature and the boiling points of the components in the melt.

[0079] Stage 3: With the chamber under vacuum, the mounted preform is allowed to completely immerse itself by gravity into the liquid aluminum bath as the aluminum melts. The melting temperature of the metal is 660°C for pure aluminum, or lower for aluminum alloys depending on the alloying elements.

[0080] Stage 4: Once the VPT furnace has reached a temperature above 900°C, apply positive inert gas pressure and keep the temperature and pressure constant until the displacement reaction is complete. Argon or helium gas is preferably used in the pressure range of 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or higher.

[0081] Stage 5: With the chamber still under positive pressure, the shape is allowed to cool to a temperature just above the solidification temperature of the aluminium, again above 660°C for pure aluminium and below for aluminium alloys.

[0082] Stage 6: While the VPT furnace is held at a temperature just above the solidification temperature of the aluminum, the pressure in the chamber is reduced to ambient atmospheric pressure, the chamber is opened, the ceramic-metallic composite shape is extracted from the liquid metal bath, and the crucible is removed from the furnace.

[0083] After the first VPT furnace cycle, the ceramic-metallic shape must be processed through a second VPT furnace cycle in order to eliminate centerline porosity via a remelt-repressurization process. This second VPT furnace cycle is essentially made up of seven stages.

[0084] Stage 1: At ambient atmospheric pressure, a composite shape is loaded into an empty VPT furnace and the chamber is then sealed.

[0085] Stage 2: The chamber is evacuated and then the heating system is started to heat the composite shape. Medium vacuum (25 torr) or high vacuum (1×10 -3 ~1×10 -9 torr) is recommended.

[0086] Stage 3: Before the metals in the composite reach their melting temperature, positive pressure is applied using an inert gas such as argon or helium. This temperature is 660°C for pure aluminum and lower for aluminum alloys, depending on the alloying elements. An inert gas should be used at a pressure ranging from 0.3 MPa (50 psi) to 6.9 MPa (1000 psi) or higher.

[0087] Stage 4: Under positive inert gas pressure, a heating system raises the temperature of the shape above the melting temperature of the metal in the composite.

[0088] Stage 5: With the chamber under positive pressure, the temperature and pressure are held constant until all voids have been eliminated from the composite shape.

[0089] Stage 6: The shape is allowed to cool while the chamber remains under positive pressure.

[0090] Stage 7: Once the shape temperature has dropped below the solidification temperature of aluminum, the pressure in the VPT furnace is reduced to ambient atmospheric pressure, the chamber is opened, and the final ceramic-metallic composite shape is removed. This temperature is 660°C for pure aluminum and lower for aluminum alloys depending on the alloying elements. The final composite has no centerline voids and improved properties.

[0091] Below are examples of these preferred embodiments of the invention. EXAMPLES

[0092] Example 1: A test bar shape of a preform containing 36 wt% silicon dioxide (SiO2) and 64 wt% silicon carbide (SiC) was prepared by conventional methods. The preform shape and a crucible containing an alloy of 80 wt% aluminum and 20 wt% silicon were loaded into a vacuum-pressure-transformation furnace. The VPT furnace was then sealed and the chamber was filled with 1×10 -4A high vacuum of 1000 torr was pulled. Still under this negative pressure, the preform was held above the crucible by an actuator and a heating system preheated the preform shape to a temperature of 900°C to melt the Al-Si alloy. Once 900°C was reached, the vacuum was reduced to a medium vacuum of 5 torr. Once both the preform shape and the aluminum alloy were heated to 1200°C, still under this negative pressure, the preform was fully immersed in the liquid Al-Si bath by an actuator. Once the shape was fully immersed in the liquid metal bath, a positive pressure of inert argon gas was applied. The temperature was held at 1200°C and the pressure was held at 5.0 MPa (725 psi) for 90 minutes, at which point the transformation was complete and a speed of 8.5 mm / hour was achieved. With the chamber maintained at this positive pressure, the actuator pulled the shape completely out of the liquid aluminum bath and then allowed to cool to below 450°C. After reducing the pressure in the VPT furnace to ambient atmospheric pressure, the chamber was opened and the SiC-Al2O3-Al ceramic-metallic composite shape was removed. The test bars were measured for flexural strength and apparent porosity according to ASTM standards C1161 and C20. The three-point flexural strength was 423 MPa (61,400 psi) and the apparent porosity was zero. The final composite had no centerline voids, as determined by weighing its density, and had a structure similar to that seen in Figures 2 and 4.

[0093] Example 2: Two preform test bar shapes containing 36 wt% SiO2 and 64 wt% SiC were conventionally prepared. The preform shapes were mounted in a fixture and placed over a crucible containing a solid 80 wt% Al and 20 wt% Si alloy, all at room temperature. The crucible and fixture assembly was loaded into a vacuum-pressure-transformation furnace. The VPT furnace was sealed and the chamber was filled with 1×10 -4A high vacuum of 1000 torr was drawn. While still under this negative pressure, the preform shape and the Al-Si alloy were heated to a temperature of 900°C. At some point above 577°C, the Al alloy melted and the fixture and the two preform shapes were completely immersed in the liquid metal bath by gravity. Once 900°C was reached, the vacuum was reduced to a medium vacuum of 5 torr. Once the alloy bath reached 1200°C, a positive inert argon gas pressure of 7.0 MPa (1015 psi) was applied for 90 minutes. With the chamber maintained at this positive pressure, the liquid metal was then allowed to cool to 700°C or above its solidification temperature. At that point, the pressure in the VPT furnace was reduced to ambient atmospheric pressure, the chamber was opened, the fixture was removed from the liquid metal bath, the SiC-Al2O3-Al ceramic-metallic composite shape was removed from its fixture, and the crucible was removed from the furnace. One test bar was removed and left as is, whereas the second test bar was run through a second VPT furnace cycle for remelting-repressurization. Still at ambient atmospheric pressure, the composite shape was loaded into the VPT furnace (after removing the crucible and metal) and the chamber was then sealed. The chamber was filled with 1×10 -4A high vacuum of 1000 torr was then drawn and the furnace started to heat the composite shape. This negative pressure was maintained until the shape reached 400°C, then a positive inert argon gas pressure of 7.0 MPa (1015 psi) was applied. Heating continued until the shape reached 700°C, then the test bar was held at that temperature for 90 minutes. Still maintaining a positive pressure, the shape was allowed to ramp down to a temperature of 400°C. At that point, the pressure in the VPT furnace was reduced to ambient atmospheric pressure, the chamber was opened, and the final ceramic-metallic composite shape was removed. The flexural strength and apparent porosity of both test bars were measured according to ASTM standards C1161 and C20. The test bar processed in a single pass through the VPT furnace had a three-point flexural strength of 275 MPa (39,900 psi), an apparent porosity of 1.5% by volume, and centerline voids similar to those seen in Figures 1 and 3. In contrast, the test bars processed through the VPT furnace twice had a three-point bend strength of 420 MPa (61,000 psi), zero apparent porosity as measured by weighing density, and had a structure similar to that seen in Figures 2 and 4 with no centerline voids.

[0094] Example 3: A preform rod shape comprising silicon dioxide (SiO2) was prepared by conventional methods. The preform shape and a crucible containing commercially pure aluminum were loaded into a vacuum-pressure-transformation furnace. The VPT furnace was then sealed and the chamber was filled with 1×10 -4A high vacuum of 1000 torr was pulled. Still under this negative pressure, the actuator held the preform over the crucible and a heating system preheated the preform shape to a temperature of 900°C to melt the aluminum. Once 900°C was reached, the vacuum was lowered to a medium vacuum of 5 torr. Once both the preform shape and the aluminum alloy were heated to 1200°C, still under this negative pressure, the actuator fully immersed the preform in the liquid aluminum bath. Once the shape was fully immersed in the liquid metal bath, a positive pressure of inert argon gas was applied. The temperature was held at 1200°C and the pressure was held at 5.0 MPa (725 psi) for 90 minutes. With the chamber still at this positive pressure, the actuator fully removed the shape from the liquid aluminum bath and then allowed to cool to below 600°C. After the pressure in the VPT furnace was reduced to ambient atmospheric pressure, the chamber was opened and the Al2O3-Al ceramic-metallic composite shape was removed. The final composite had no centerline voids as determined by density weighing.

[0095] Example 4: A preform rod shape containing SiO2 was prepared by conventional methods. The preform shape and a crucible containing an alloy of 60 wt% aluminum and 40 wt% silver (Ag) were loaded into a vacuum-pressure-transformation furnace. The VPT furnace was then sealed and the chamber was filled with 1×10 -4A high vacuum of 1000 torr was pulled. Still under this negative pressure, the preform was held above the crucible by an actuator and a heating system preheated the preform shape to a temperature of 900°C to melt the aluminum alloy. Once 900°C was reached, the vacuum was reduced to a medium vacuum of 10 torr. Once both the preform shape and the alloy were heated to 1200°C, still under this negative pressure, the actuator fully immersed the preform in the liquid Al-Ag bath. Once the shape was fully immersed in the liquid metal bath, a positive pressure of inert argon gas was applied. The temperature was held at 1200°C and the pressure was held at 1000 psi for 90 minutes. With the chamber still at this positive pressure, the actuator fully removed the shape from the liquid aluminum bath and then allowed to cool to below 550°C. After the pressure in the VPT furnace was reduced to ambient atmospheric pressure, the chamber was opened and the Al2O3-Al-Ag ceramic-metallic composite shape was removed. The final composite had no centerline voids as determined by density weighing.

[0096] Example 5: A preform rod shape containing SiO2 was prepared by conventional methods. The preform shape and a crucible containing an alloy of 85 wt% aluminum and 15 wt% iron (Fe) were loaded into a vacuum-pressure-transformation furnace. The VPT furnace was then sealed and the chamber was filled with 1×10 -4A high vacuum of 1000 torr was drawn. Still under this negative pressure, the actuator held the preform over the crucible and a heating system preheated the preform shape to a temperature of 900°C to melt the aluminum alloy. Once 900°C was reached, the vacuum was reduced to a medium vacuum of 7.5 torr. Once both the preform shape and the alloy were heated to 1200°C, still under this negative pressure, the actuator fully immersed the preform into the liquid Al-Fe bath. Once the shape was fully immersed in the liquid metal bath, a positive pressure of inert argon gas was applied. The temperature was held at 1200°C and the pressure was held at 5.0 MPa (725 psi) for 90 minutes. With the chamber still at this positive pressure, the actuator fully removed the shape from the liquid aluminum bath and then allowed to cool to below 650°C. After the pressure in the VPT furnace was reduced to ambient atmospheric pressure, the chamber was opened and the Al2O3-Al-Fe ceramic-metallic-intermetallic composite shape was removed. The final composite had no centerline voids as determined by density weighing.

Claims

1. 1. A method for producing a ceramic-metallic composite material without centerline voids, comprising: a) The following: i) a chamber having an access door; ii) a crucible within said chamber; iii) a source of inert gas connected to the chamber and a pressurization system for selectively pressurizing the chamber with the inert gas; iv) a vacuum pump system connected to the chamber and capable of selectively evacuating the chamber; and v) a heating system capable of selectively heating and operating the chamber; providing a vacuum-pressure-transformation (VPT) furnace comprising: b) adding a charge of aluminum or an aluminum alloy into the crucible; c) placing a preform object in the chamber above the crucible, the preform object having an unenclosed side directly exposed to an interior of the chamber; d) operating the vacuum pumping system to create a partial vacuum in the chamber; e) operating the heating system while under partial vacuum in the chamber to raise the chamber temperature above the melting point of the charge, thereby melting the charge and heating the preform to the same temperature as the charge; f) immersing the preform into the molten charge in the crucible; g) operating the pressurization system to pressurize the chamber with the inert gas to a pressure greater than 0.3 MPa; h) maintaining the temperature and pressure constant until the displacement reaction is complete; i) reducing the temperature within the chamber while maintaining a positive pressure within the chamber and extracting the now ceramic-metallic composite shape from the crucible; and j) allowing the composite shape to cool under positive pressure; and k) removing the ceramic-metallic composite shape from the chamber, the composite shape being free of centerline voids; The method includes:

2. The method of claim 1 , wherein the placing step includes attaching the preform article to a fixture.

3. The method of claim 1 , wherein the inert gas is selected from the group consisting of argon and helium.

4. The method of claim 2 , wherein the fixture is mounted on an actuator.

5. The method of claim 4 , wherein the immersing step includes the step of operating the actuator to lower the preform article into the crucible.

6. The method of claim 1 , wherein the immersion step includes lowering the preform article into the crucible by gravity.

7. The step of operating the vacuum pump system includes first pumping the chamber to 1×10 psi until the charge inside the crucible melts. -3 ~1×10 -9 2. The method of claim 1, comprising evacuating the chamber to a pressure of about 0.001 torr and then increasing the pressure to between 0.001 and 25 torr.

8. The method of claim 1 , wherein the step of operating the pressurization system includes pressurizing the chamber to a pressure of 0.3 to 6.9 MPa.

9. 10. The method of claim 1, wherein the method is carried out at a reaction rate of at least 8.5 mm / hr.

10. The method of claim 1 , wherein the heating system is operated to raise the temperature of the chamber to greater than 900° C.

11. The method of claim 1 , wherein the ceramic-metallic composite shape is extracted from the crucible at a temperature above the melting point of aluminum.

12. 12. The method of claim 11, a) the crucible is removed from the chamber and the ceramic-metallic composite shape is reloaded into the chamber; b) the vacuum pumping system is activated to reduce the chamber pressure to below 25 torr; c) heating the chamber to just below the melting point of the shape and activating the pressurization system to flow inert gas into the chamber to a pressure of at least 0.3 MPa; d) increasing the chamber temperature above the melting temperature of the metal in the shape; e) holding the temperature constant until all voids have been removed from the shape; f) cooling the shape in the chamber with positive pressure; and g) Removing the shape from the chamber. method.

13. 13. The method of claim 12, wherein the inert gas is selected from the group consisting of argon and helium.

14. The method of claim 12, wherein the pressure is from 0.3 to 6.9 MPa.

15. 13. The method of claim 12, wherein prior to step g) removing the shaped object from the chamber, the temperature within the chamber is maintained above a solidification temperature of aluminum.

16. 16. The method of claim 15, further comprising reducing the pressure in the chamber to ambient atmospheric pressure prior to step g) of removing the shaped object from the chamber.

17. 1. A method for producing a ceramic-metallic composite material without centerline voids, comprising: a) The following: i) a chamber having an access door; ii) a crucible within said chamber; iii) a source of inert gas connected to the chamber and a pressurization system for selectively pressurizing the chamber with the inert gas; iv) a vacuum pump system connected to the chamber and capable of selectively evacuating the chamber; and v) a heating system capable of selectively heating and operating the chamber; providing a vacuum-pressure-transformation (VPT) furnace comprising: b) adding a charge of aluminum into the crucible; c) placing a preform object in a fixture on an actuator into the chamber, above the crucible, the preform object having an unenclosed side directly exposed to the interior of the chamber; d) operating the vacuum pumping system to create a partial vacuum in the chamber; e) operating the heating system while in the partial vacuum state of the chamber to raise the chamber temperature to greater than 900° C., thereby melting the aluminum charge and heating the preform to the same temperature as the charge; f) operating the actuator to immerse the preform into the liquid aluminum inside the crucible; g) operating the pressurization system to pressurize the chamber with the inert gas selected from the group consisting of argon and helium to a pressure greater than 0.3 MPa; h) maintaining the temperature and pressure constant until the displacement reaction is complete; i) reducing the temperature within the chamber while maintaining a positive pressure within the chamber and operating the actuator to eject the now ceramic-metallic composite shape from the crucible; j) allowing the composite shape to cool under positive pressure; and k) removing the ceramic-metallic composite shape from the chamber, the composite shape being free of centerline voids; The method includes:

18. 20. The method of claim 17, wherein the immersing step includes the step of operating the actuator to lower the preform article into the crucible.

19. The step of operating the vacuum pump system includes first pumping the chamber to 1×10 psi until the aluminum inside the crucible melts. -3 ~1×10 -9 18. The method of claim 17, comprising evacuating the chamber to a pressure of about 0.001 torr and then increasing the pressure to between 0.001 and 25 torr.

20. 1. A method for producing a void-free ceramic-metallic composite material, comprising: a) The following: i) a chamber having an access door; ii) a crucible within said chamber; iii) a source of inert gas connected to the chamber and a pressurization system for selectively pressurizing the chamber with the inert gas; iv) a vacuum pump system connected to the chamber and capable of selectively evacuating the chamber; and v) a heating system capable of selectively heating and operating the chamber; providing a vacuum-pressure-transformation (VPT) furnace comprising: b) adding a charge of aluminum into the crucible; c) placing a preform in a fixture on an actuator into said chamber, above said crucible; d) operating the vacuum pumping system to create a partial vacuum in the chamber; e) operating the heating system to raise the chamber temperature to greater than 900° C., thereby melting the aluminum charge; f) operating the actuator to immerse the preform into the liquid aluminum inside the crucible; g) operating the pressurization system to pressurize the chamber with the inert gas selected from the group consisting of argon and helium to a pressure greater than 0.3 MPa; h) maintaining the temperature and pressure constant until the displacement reaction is complete; i) reducing the temperature within the chamber while maintaining a positive pressure within the chamber and operating the actuator to eject the now ceramic-metallic composite shape from the crucible at a temperature above the melting point of aluminum; j) allowing the composite shape to cool under positive pressure; k) removing the ceramic-metallic composite shape from the chamber; l) the crucible is removed from the chamber and the ceramic-metallic composite shape is reloaded into the chamber; m) the vacuum pumping system is activated to reduce the pressure in the chamber to below 25 torr; n) heating the chamber to just below the melting point of the shape and activating the pressurization system to flow an inert gas into the chamber to a pressure of at least 0.3 MPa; o) increasing the chamber temperature above the melting temperature of the metal in the shape; p) holding the temperature constant until all voids have been removed from the shape; q) cooling the shape in the chamber under positive pressure; and r) removing said shape from said chamber; The method includes:

Citation Information

Patent Citations

  • Production of high strength composite metallic material

    JP1983151439A

  • Casting method for metal matrix composite castings

    US5394930A